The effect of implementation of evidence-based eye care protocol for patients in the intensive care units on superficial eye disorders - Azam Pourghaffari Lahiji; Mohsen Gohari; Samaneh Mirzaei; Khadijeh Nasiriani (BMC Ophthalmology, 2021)
Abstract Background Superficial eye disorders are one of the most common complications of improper eye care in intensive care units that can lead to corneal ulcers and permanent eye damage. The aim of this study was to determine the effect of the implementation of eye care protocol on the incidence of infection and superficial eye disorders in patients admitted to intensive care units. Methods This study was a cross-over clinical trial that was performed on 32 patients admitted to the intensive care unit with reduced or no blink reflex following loss of consciousness or receiving sedatives. The eye of the test group received eye care according to the protocol and the eye of the control group received the routine care of the ward. The data collection form included demographic and clinical information and the clinical score scale of superficial eye disorders, which were completed in 7 days for both eyes. Data analysis was performed by McNemar and Cochran tests with a 95 % confidence interval. Results In the study of superficial eye disorders, the frequency of dacryorrhea and hyperemia was not significantly different in the second to seventh days in the control and test eyes (P < 0.05). The frequency of xerophthalmia was not significantly different between the control and the test eyes on the second to third days (P < 0.05), but there was a significant difference on the fourth, fifth, sixth, and seventh days (P = 0.0001). Also, the frequency of corneal opacity was not significantly different in the second and third days (P < 0.05), but in the fourth (P < 0.05), fifth, sixth, and seventh days, this difference was significant (P = 0.0001). Conclusions Based on the results, although the implementation of eye care protocol has been able to have a significant effect on reducing ocular complications and problems, routine eye care in the intensive care unit also has clinical effectiveness. Therefore, in order to prevent and completely eliminate eye disorders in the intensive care unit, more evidence and research are needed. Trial registration The trial was retrospectively registered on https://en.irct.ir/trial/43493 on 13 November 2019 (13.11.2019) with registration number [IRCT20140307016870N5].